SCHOOL INNOVATION MANAGEMENT IN DEVELOPING A DIGITAL LEARNING ECOSYSTEM - Marilin Kristina; Ruly Nadian Sari; Miswan Gumanti; Rara Marselina Jupon (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Bahasa Institut Pendidikan Tapanuli Selatan, 2026)
Digital transformation in education requires schools to manage innovation systematically to build an effective, sustainable, and adaptive digital learning ecosystem. This study aims to analyze school innovation management in developing digital learning ecosystems, focusing on planning, implementation, resource management, and sustainability strategies. A mixed-methods explanatory sequential design was applied, beginning with a quantitative survey of teachers, followed by qualitative interviews with school leaders and innovation teams. The results reveal three key determinants of ecosystem effectiveness: innovative leadership, digital resource readiness, and a collaborative school culture. Schools that integrated data-driven decision-making, continuous teacher professional development, and adequate digital infrastructure demonstrated stronger ecosystem performance. These findings emphasize the critical role of innovation management as the foundation for creating an adaptive, inclusive, and high-quality digital learning ecosystem.